The importance of molecular markers for diagnosis and selection of targeted treatments in patients with cancer. (16th September 2015) - Tobin, N. P.; Foukakis, T.; De Petris, L.; Bergh, J.
Abstract: The past 30 years have seen the introduction of a number of cancer therapies with the aim of restricting the growth and spread of primary and metastatic tumours. A shared commonality among these therapies is their targeting of various aspects of the cancer hallmarks, that is traits that are essential to successful tumour propagation and dissemination. The evolution of molecular‐scale technology has been central to the identification of new cancer targets, and it is not a coincidence that improved therapies have emerged at the same time as gene expression arrays and DNA sequencing have enhanced our understanding of cancer genetics. Modern tumour pathology is now viewed at the molecular level ranging from IHC biomarkers, to gene signature classifiers and gene mutations, all of which provide crucial information about which patients will respond to targeted therapy regimens. In this review, we briefly discuss the general types of targeted therapies used in a clinical setting and provide a short background on immunohistochemical, gene expression and DNA sequencing technologies, before focusing on three tumour types: breast, lung and colorectal cancers. For each of these cancer types, we provide a background to the disease along with an overview of the current standard therapies and then focus on the relevant targeted therapies and the pathways they inhibit. Finally, we highlight several strategies that are pivotal to the successful development of targeted anti‐cancer drugs.